The Relationship Between Pregnant Women's Anxiety About Having Sex During Pregnancy At Amini Dalan Lidang Clinic, Panyabungan District Mandailing Natal Country Year 2023 - Dewi Sri Rahayu Tinendung (Sean Institute, 2023)
Sexual intercourse during pregnancy is individual and is influenced by physical factors, emotions, sexual dysfunction, and myths about sex while pregnant. During pregnancy most of the desire to have sex does not change, in fact, increasing, because it is influenced by the increase in the hormone estrogen. Therefore, sexual intercourse during pregnancy is not a nuisance. Sexual intercourse during pregnancy can still be done, but for the first trimester of pregnancy. The frequency of having sex should not be done as often as usual. If sexual intercourse is forced in the first trimester of pregnancy, it is feared that spontaneous miscarriage may occur. This study aims to determine the relationship between the level of anxiety of pregnant women about having sex during pregnancy at the Amini Clinic in Lidang, Panyabungan District, Regency Mandailing Christmas Year 2023 . The type of research used is a descriptive study with a cross sectional approach The population in the study was pregnant who checked their pregnancy at the midwife Amini clinic in lidang. The sampling technique uses Random Sampling with a sample size of 41 people. Data collection using primary and secondary data. Data analysis using chi-square test with significant level of p<0.05. The results of the analysis showed that there was a relationship between the level of anxiety of pregnant women about having sex during pregnancy with a value of P = 0.001 where P = <0.05. It is expected that pregnant women are advised to still want to have sexual relations during pregnancy appropriately to maintain family harmony and meet physiological needs and for health workers at the midwife clinic Amini can provide counseling about sexuality during pregnancy either by giving counseling on sexuality during pregnancy either by giving IEC at the time of pregnancy check-up or counseling at the posyandu.